Catalytic upgrading of cow manure pyrolysis vapors over zeolite/carbon composites prepared from coal gasification fine slag: High quality bio-oil obtaining and mechanism investigation. (1st May 2023) - Wu, Ruofei; Lv, Peng; Wang, Jiaofei; Bai, Yonghui; Wei, Juntao; Song, Xudong; Su, Weiguang; Yu, Guangsuo
Highlights: Different zeolite/carbon composites were prepared from coal gasification fine slag. Catalytic pyrolysis of cow manure over zeolite/carbon composites was evaluated. Relationship between catalysts structure and product selectivity was clarified. Mechanism of cow manure pyrolysis vapors to light aromatics was revealed. Model amino acids used to study the mechanism of nitrogen species transformation. Abstract: The resource utilization of solid waste not only reduces the environmental pollution, but also reduces the use of fossil energy. In this study, three low-cost zeolite/carbon composites, including Y-type zeolite/carbon, Beta zeolite/carbon and ZSM-5 zeolite/carbon, were prepared from coal gasification fine slag (CGFS), which were used for catalytic upgrading of pyrolysis vapors of cow manure (CM). The composition and distribution of products from the catalytic pyrolysis of CM over different types composites were explored, and the relationship between catalysts structure and product selectivity was clarified. The results show that different types of catalysts have virous effects on the composition and distribution of products due to different physiochemical structures such as pore size and acid site. Among them, ZSM-5 zeolite/carbon is more conducive to the formation of monocyclic aromatics due to its shape selective catalysis, Beta zeolite/carbon has relatively large pore size and has high selectivity for polycyclic aromatics, and Y-type zeolite/carbon is more conducive to the removal of nitrogen and oxygen-containing compounds. Moreover, vanillin, glucose and valine, which are the main components of lignin, cellulose and protein in CM were selected as model compounds to reveal the reaction mechanism of catalytic upgrading. The results of this study can provide reference and theoretical guidance for the comprehensive utilization of solid waste and the development of low-carbon green industry.